High resolution geochemical and grain-size analysis of the AD 1755 tsunami deposit: Insights into the inland extent and inundation phases - Moreira, Sandra; Costa, Pedro J.M.; Andrade, César; Ponte Lira, Cristina; Freitas, Maria Conceicao; Oliveira, Maria Alexandra; Reichart, G.J. (Elsevier BV, 2017)
In the study of palaeotsunamis it is crucial to decipher the sedimentological record, to derive intensity of past events and to infer different inundation phases. To achieve this goal, it is important to apply high-resolution techniques that allow magnifying intra-deposit details (at a sub-centimetric scale) that otherwise would not be perceived; consequently, valuable information could be overlooked. In this work, we applied successfully high-resolution geochemical and grain-size analyses – XRF core-scanning and image analysis, respectively – to the AD 1755 tsunami deposit. This quartz sand enriched in bioclast deposit (exhibiting high Si/Al and Ca/Ti) was recognized in the coastal stratigraphic sequence of Salgados lagoon due to its contrasting composition when compared with the under and overlying mud layers with scarce bioclasts (exhibiting low Si/Al and Ca/Ti). In the absence of textural evidence, the identification of peaking concentrations of Cl, S and Br (all major constituents of sea salt) in a continuous muddy sequence allowed slightly extending farther inland the limit of inundation. In addition, grain-size analysis data attested the fining inland of the deposit. Furthermore, despite the macroscopic massive structure of the tsunami deposit, throughout the lagoon, grain-size results revealed more complexity and allowed inferring up to four depositional sequences directly associated with the AD 1755 tsunami inundation.
Keywords: Geochemistry; Grain-size image analysis; Palaeotsunami; Inundation; Backwash; Portugal; A D 1755 tsunami; Taverne